Phaseolus germplasm exploration in New Mexico and Trans-Pecos of Texas, USA - Debouck, Daniel; Dohle, Sarah; Guerrero-Florez, Gabriela; Porch, Timothy; Pratt, Richard; Santos Melendez, Luis Guillermo (2025)
Given the poor representation of wild bean accessions from the Trans-Pecos region of Texas in genebanks (seven accessions from two localities), a nine-day germplasm exploration was carried out in an area covering the counties of Doña Ana, Otero and Eddy in New Mexico and El Paso, Culberson and Jeff Davis in Texas. Twenty-three populations were collected, out of which 17 were wild tepary, three of P. filiformis, two of P. angustissimus and one of P. grayanus. Seed, herbarium and soil samples were collected for all populations.